The Mutual Fund Performance, Before, During, and After the Financial Crisis: Evidence from GCC Region - Hamdan, Rana (2020)
Mutual fund is a pool of the investors’ money who share a common financial goal. Mutual fund offers an opportunity to invest in diversified, professionally managed basket of financial assets. Risk and performance assessment is a vital interest for investors as it offers optimal risk adjusted returns to investors, this is also an important area for mutual funds managers to use the information to make their investment decisions. This makes the risk and performance an attractive area for the researchers. This study aims to analyze the performance of Saudi Arabia open-end fund. A sample of 12 equity mutual funds is used in this study during the period January 2000 to December 2018. The analysis over the 18 years included an important financial event which is the global financial crisis, therefore, the study investigates the impact of global financial crisis on the performance of the mutual funds. The study employs the most important and widely used risk adjusted performance measures including Sharpe ratio, Treynor ratio, Jensen Alpha, M2 and information ratio. The result shows that few funds had outperformed the market, while the rest had underperformed during the study period. Some funds could not been able to beat the risk-free rate. On average the funds had returned lower than the expected return from CAMP. Some managers could manage the fund probably during the three period and led their funds to pass through the economic crisis with minimal losses.